Impact of sentiment indicators on the capital market dynamics and default probability - Stoykova, Ani Qankova; Paskaleva, Mariya Georgieva; Stoykov, Dinko Zhulien (International Journal of Contemporary Economics and Administrative Sciences, 2018)
This paper examines the impact of sentiment indicators on the financial market dynamics and default probability. First, we use GARCH models and Granger Causality Test in order to test the relationship between sentiment indicators and capital market dynamics of eleven Southeastern European countries. Second, we employ GARCH models and Granger Causality Test to examine the influence of sentiment indicators on the sovereign credit risk in Bulgaria. The analyzed period is from January 2005 to November 2015. The results reveal that the consumer sentiment information and inflation expectations have influence on the financial market dynamics of SEE stock indices. Test results present that sentiment variables may explain CDS spread changes efficiently. We observe bilateral relations, which may be accepted as proves that turmoil periods may be led by panic and fear of investors without any enormous change in other factors.